PAK ORANG DEWASA: KARAKTER ISTRI KRISTEN BERDASARKAN TITUS 2:4-5 - Siburian, Hendro Hariyanto (CARAKA: Jurnal Teologi Biblika dan Praktika, 2024)
Every Christian wife is obliged to have good character according to God's Word. Therefore it is very important to know the Bible's teachings about the character of a Christian wife. Through Christian religious education for adults, teaching about the character of a wife can be done. The purpose of this article is to explore teachings about the character of Christian wives based on Titus 2:4-5. In accordance with the aim of the author, this article uses qualitative methods with a literature study approach and text exposition study. The results of this research reveal that a Christian wife in Titus 2:4-5 is a wife who loves her husband and children, lives wisely and chastely, diligently manages her household, is kind and obedient to her husband. If every Christian wife has this character, then the Christian family will be harmonious and pleasing before the Lord Jesus.